Digital strategy aligning in SMEs: a dynamic capabilities perspective. - Canhoto, Ana Isabel; Quinton, Sarah; Pera, Rebecca; Molinillo-Jiménez, Sebastián; Simkin, Lyndon (My University, 2021)
Digital strategy alignment is a dominant concern for today’s managers and information systems researchers. Yet research in this area remains fragmented, particularly on the digital strategy alignment of small and medium-sized enterprises (SMEs), which is concerning owing to their value to European economies. Employing dynamic capabilities as an analytical lens, we investigate how 43 British, Irish, Italian, and Spanish SMEs, across five industry sectors, enact digital aligning. We identify a model of digital alignment comprising five phases, which we term “passive acceptance,” “connection,” “immersion,” “fusion,” and “transformation,” as well as the specific combinations of sensing, seizing, and reorganizing capabilities associated with each phase. Our model provides a holistic, practice-based perspective and highlights the role of micro-behaviors and leadership in SMEs implementing digital strategy.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14184 (submitted version)
Keywords: Pequeñas y medianas empresas - Innovaciones tecnológicas; Digital strategy aligning; SMEs; Europe; Dynamic capabilities; Five-phase model